Etiology, Risk Factors, and Antimicrobial Resistance in Recurrent Pyogenic Liver Abscesses: A Six-Year Analysis - Cui J; Liu Y; Fu H; Cui M; Li J; Bai Z; Li J (Infection and Drug Resistance)
JinHua Cui,1 YaMan Liu,2 Hua Fu,1 MiaoHang Cui,1 JiZhong Li,3 ZiYu Bai,1 Jian Li1 1Department of Hepatobiliary Surgery, Affiliated Hospital of Chengde Medical College, Chengde City, Hebei Province, People’s Republic of China; 2Department of Gynaecology, Affiliated Hospital of Chengde Medical College, Chengde City, Hebei Province, People’s Republic of China; 3Department of Operating Room, Affiliated Hospital of Chengde Medical College, Chengde City, Hebei Province, People’s Republic of ChinaCorrespondence: Jian Li, Department of Hepatobiliary Surgery, Affiliated Hospital of Chengde Medical College, Chengde City, Hebei Province, People’s Republic of China, Email lijian111008@126.comAim: To perform a comparative analysis of the clinical data of patients with and without recurrent pyogenic liver abscess and explore the influencing factors, clinical characteristics, and pathogenic bacteria associated with the recurrence of liver abscesses.Patients and Methods: A retrospective analysis was conducted on 436 recently diagnosed patients with pyogenic liver abscess admitted to the Affiliated Hospital of Chengde Medical College between June 2017 and June 2023. Patients with recurrence comprised the observation group, whereas those without recurrence comprised the control group.This analysis included the examination of clinical characteristics, pathogens, drug resistance patterns, and treatment modalities. Additionally, regression analysis was employed to investigate the factors influencing liver abscess recurrence.Results: Of 436 patients initially diagnosed with pyogenic liver abscess, 58 experienced recurrence. The proportion of Escherichia coli infection was 23.3% in the observation group and 10.3% in the control group, indicating a statistically significant difference. Multivariate analysis identified diabetes mellitus and cerebral infarction as significant risk factors for recurrent pyogenic liver abscess.Conclusion: In comparison with patients without recurrence, those who experienced recurrent pyogenic liver abscess following initial diagnosis exhibited a higher prevalence of E. coli as a pathogenic bacterium. In addition, a history of diabetes mellitus and cerebral infarction are high-risk factors for with pyogenic liver abscess recurrence for the first time.Keywords: pyogenic liver abscess, relapse, Klebsiella pneumoniae, Escherichia coli, diabetes mellitus